Digital transformation and the advancement of industry 4.0 in Peruvian companies - Díaz-Garay, Bertha Haydeé (2025)
Digital transformation and Industry 4.0 represent a revolution in business models, production processes, and information management, driven by the development and application of advanced technologies. This study aimed to explore the state of digital transformation in Peruvian companies from the perspective of their leaders. The research had an exploratory and descriptive scope, with a mixed-methods approach, and focused on identifying the progress of digital transformation processes within organizations. A sample of 20 large companies was considered: 18 located in the Lima region and 2 in the highlands. Through a survey, their management models, human talent, methodologies, and technologies used were analyzed. The results revealed that a company’s digital maturity is closely linked to its human capital, digital methodologies, and the technologies it employs. It was also found that the impact of digital transformation largely depends on the organization’s digital maturity and the capabilities of the people involved. Companies leading this change have achieved better outcomes, particularly in customer focus and process efficiency. The key areas where digital technologies are most applied include data-driven decision-making, collaborative learning, the exploration of new digital opportunities, and cybersecurity.